The Role of Community Radio in Empowering and Engaging Community Population in Kerala - A, Roshni K; G, Karthika; Babu, S. Dinesh (International Journal of Psychosocial Rehabilitation, 2020)
Community radio: A revolution that brings about changes in communities. When it comes to what makes community radio relevant in this era, community radio as a mass medium has a lot to do with weaving together the marginalized sections of a society to a powerful level and give impetus to rural development related issues. It is a very reliable and powerful tool for social change. Community Radio speaks the dialect of the local community for easy communication. This research paper will discuss how community radios in Kerala can serve as an effective and interactive medium in the current context to raise awareness and empower different communities. In doing so, this study helps to understand the role of community radio as a medium for social change. Quantitative methods and qualitative methods of interpretation were used for this purpose. Surveys and case study approaches were conducted to meet the objectives. In addition, the nature of programs provided by community radio was evaluated. Data for the study were collected from responses from various community radio stations in Kerala, from various journals and websites.While community radio provides a platform for citizens to express themselves in the public sphere, the study shows that community radio is less relevant in Kerala society, which is at the forefront of literacy and social development. This study, which assesses the broad potential of community radio in engaging and empowering rural people across Kerala, brings a new dimension.